THEORY AND PRACTICE OF RUSES OF WAR IN MILITARY AFFAIRS - Pegahin І. А.; Starodybcev S. О.; Chyhlaty А. V.; Varakyta, V. P. (Honor and Law, 2019)
Military cunning considered as a category of martial arts, determined forms, methods and techniques of its use in planning (the plan) and conduct combined arms (hostilities).